Penerapan Metode Fuzzy Time Series Using Percentage Change - Nurul Hidayah; Ika Purnamasari; Memi Nor Hayati (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
In 1993, Song and Chissom introduce fuzzy times series is capable of handling the problem of data forecasting if historical data are the values ​​of linguistic. The study uses the modeling outline by way of fuzzy relation equations and approximate reasoning to predict the number of students. In this study, the approach to the theory of fuzzy time series used is fuzzy time series using percentage change developed by Stevenson and Porter in 2009. The case studies used in this study is the population of East Kalimantan Province. This study aims to determine how the application of fuzzy time series method using percentage change in the population of East Kalimantan from 1980 until 2013. Forecasting is done menggukan linguistic value of the fuzzy set which is formed of the differences and converted into a percentage of the universe of discourse as a value data. Based on the results of the application of the method using fuzzy time series of the percentage change obtained 12 fuzzy set which is linguistics of the data, the accuracy of forecasting value from 1981 to 2013 using MAPE (Avarage Forcasting Error Rate) that is equal to 0.557%.